Urban Gardening and Green Space Governance: Towards New Collaborative Planning Practices - Sofia Nikolaidou; Tanja Klöti; Simone Tappert; Matthias Drilling (Urban Planning, 2016)
In the context of urban densification and central urban areas’ lack of open spaces, new forms of small-scale urban gardening practices have emerged. These gardening practices respond to urban pressures and open new modes of green space governance, presenting alternative and multifunctional ways to manage and revitalise cities. Focusing on the case of Geneva, the article unfolds two levels of discussion. On the one hand—and with reference to the theorist Habermas—it examines how multiple actors with different interests interplay and cooperate with each other in order to negotiate over open space, while discussing implications for local politics and planning. On the other hand, it describes how these negotiations result in new, innovative, and hybrid forms of public green space. The main findings indicate emerging forms of collaboration, partnerships, and governance patterns that involve public and private sectors and increase participation by civil society actors. Cooperation amongst several interested groups and the collective re-invention of public urban spaces increase these spaces’ accessibility for multiple users and actors, as well as present possibilities for alternative and diversified uses and activities. This might underline the hypothesis that future cities will be governed in less formalised ways, and that urban forms will be created through spontaneous, temporary, mobile, and adaptive negotiation processes.